Asedios a la poética de autor - Malpartida Quispe, Miguel Ángel (2019)
This article discusses issues that are exposed in the theoretical framework of the thesis entitled The Specific Poetics of Childhood of Veloz Niño del Cielo, Veloz Niña del Alba, work presented to choose the master’s degree in Creative Writing. In the text, the objective is the definition of the concept “poetic” based on the meanings it adopts in literary studies (theoretical, prescriptive and creative) until arriving at the integral sense that will be attributed to it in the thesis: the unveiling of the creative process of the author from a critical reconstruction of that one by an interpretant and/or framed in the creator’s own voice. To clarify this concept, we first analyze the convergences between poetics, understood as an activity, and two sieves of meaning: the modern poetry and the post-avantgarde aesthetics.